Footprints of Shalmali (Bombax ceiba L.) and Mocharasa in Ayurveda therapeutics: A classical review - Vishwatej Parkhi; Pratiksha Mali; Swati Dabhi; Bhupesh Patel; Rabinarayan Acharya (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background- Plant based medicinal formulations are the integral part of classical Ayurveda therapeutics. Classical literature of Ayurved emphasizes the superiority of Dravya among the Rasadi Panchaka with various criteria. Therefore, plants and herbs are the soul of Dravyagunavigyana domain. Shalmali (Bombax ceiba L.), mentioned in Ayurveda is revered for its multipotent therapeutic utility. Objectives- This document aims to compile and study the references of Shalmali and Mocharasa in classical Ayurvedic compendia including Bruhattrayi. Further they were analyzed to gain insights into rationale present in pharmacodynamics of therapeutics of both the drugs. Methods- Classical Ayurvedic texts like Chikitsagrantha and Bruhattrayi available in central library of ITRA, Jamnagar were screened for the references of Shalmali and Mocharasa pertaining to therapeutics. Collected information of formulations was evaluated and arranged in tabular format for the ease of understanding and ready referral. Results- Shalmali and Mocharasa are used in more than 45 main and allied therapeutic indications with more than 13 parts of plant. Balashalmali and Kutashalmali are also mentioned in few instances. This proves their broad-spectrum therapeutic potential in Ayurveda therapeutics. Conclusion- This review can be utilized as ready handbook regarding the references of Shalmali and Mocharasa in Ayurvedic literature. Information revealed here is beneficial for AYUSH stakeholders like Ayurvedic researchers, practitioners and pharmacists in understanding the action mechanism of Shalmali and Mocharasa.